Factors influencing the roles of local leaders towards community development in Bamyan, Afghanistan - Salem, Faizi Mohammad (2020)
The need for local leadership is being demanded by the problems that arise in the local societies across the globe. Local leaders and agricultural extension agents should do their best of ability to solve the communities’ problem and encourage them to trust and participate in the decision-making process – controlling, planning and implementation of the development activities in their community. However, the roles of local leaders are either poor or still at the early stage in the community development, so this problem continues to be a significant one that prevails in Afghanistan’s local societies. Therefore, this study aimed at evaluating the factors that influence the roles of local leaders towards community development in Bamyan province, Afghanistan. The specific objectives were: 1) to determine the perception level of the community members towards the internal and external roles of local leaders in community development; 2) to determine the perception level of community members towards the decision-making by local leaders on community development; and 3) to identify the influencing factors among the roles assumed by the local leaders in shaping the community development decision making. A well-structured close-ended questionnaire via self-administered was used to collect primary data from 384 community members and simple randomized sampling method was used to collect primary data from three tribes (Hazara, Tajik and Sadat) in five (5) villages in Bamyan Province, Afghanistan. Both descriptive and inferential statistics were utilized for data analysis. Based on the descriptive statistics, the results showed that the roles of local leader in community development were at a moderate stage. Two components of the roles included internal roles with a total mean of 2.85 and external roles with an overall mean of 2.75. The mean for perception towards the community development by the local leader was 2.92. Factor analysis was performed to examine the underlying factors. The analysis showed that the KMO value for internal and external roles were 0.951 and 0.959, respectively and Bartlett’s test of sphericity for both was significant at the level 0.000. Therefore, the data was suitable for PCA. Out of 76 statements, statements that had more than 1.0 eigenvalue were retained. Principal component analysis using the Varimax rotation extracted eight (8) underlying factors, namely Compatibility, Decisions’ Needs, Overall Satisfaction, Development Standards, Information Collaboration, Strengthening Relationship, Immunity of Community and Attracting Sponsors. Based on the regression analysis, R2 was found to be 0.550, F test was 57.275 and three factors were found significant: decisions’ needs, immunity of the community, and attracting sponsors availability at the level of 1%, 1%, and 5%, respectively. In conclusion, the roles of local leaders in community development decision making improved from lower level to moderate level based on community members’ perception. The result also indicated that decisions’ needs, immunity and sponsors are required for community development decision-making. Therefore, this study recommends the need for support and training of the local leaders based on the above-mentioned factors to improve the condition of community development decision-making and the contribution with participation of stakeholders in decision making and implementation of development projects are essential for community development.